Experience of total knee replacement operations performed by computer-assisted navigation in Lithuania - Butėnas, Petras; Penikas, Petras; Vizgirda, Antanas; Belickas, Juozas; Uvarovas, Valentinas; Bartusevičius, Juozas; Sinkevičius, Ignas; Bartusevičius, Egidijus (Lietuvos chirurgija, 2015)
We conducted this multicentrical retrospective study in three Lithuanian hospitals to investigate the importance of using computer-assisted navigation systems during total knee arthroplasty. In this study we analyzed 143 patient navigation system registry data records from three Lithuanian hospitals who underwent a primary total knee arthroplasty operation. The multicentrical retrospective analysis period is from 2006 to 2012. The main evaluation criteria for the operation of computerassisted navigation system record data were the preoperative and postoperative mechanical axis of the limb and the knee joint function before and after surgery.
Keywords: total knee arthroplasty; computer-assisted navigation; navigation system operation registry protocol